2015
DOI: 10.1051/0004-6361/201526458
|View full text |Cite
|
Sign up to set email alerts
|

IKT 16: the first X-ray confirmed composite SNR in the SMC

Abstract: Aims. IKT 16 is an X-ray and radio-faint supernova remnant (SNR) in the Small Magellanic Cloud (SMC). A detailed X-ray study of this SNR with XMM-Newton confirmed the presence of a hard X-ray source near its centre, indicating the detection of the first composite SNR in the SMC. With a dedicated Chandra observation we aim to resolve the point source and confirm its nature. We also acquire new ATCA observations of the source at 2.1 GHz with improved flux density estimates and resolution. Methods. We perform det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
(38 reference statements)
1
15
0
Order By: Relevance
“…Such a TeV flux level is within the reach of the forthcom-ingČerenkov Telescope Array (CTA) (Martin et al 2019;Cherenkov Telescope Array Consortium et al 2019). A similar X-ray to TeV flux scaling may apply to the other PWN in the SMC, IKT 16 (Maitra et al 2015), bringing it within the reach of the CTA. ).…”
Section: Conclusion and Future Studiesmentioning
confidence: 75%
See 1 more Smart Citation
“…Such a TeV flux level is within the reach of the forthcom-ingČerenkov Telescope Array (CTA) (Martin et al 2019;Cherenkov Telescope Array Consortium et al 2019). A similar X-ray to TeV flux scaling may apply to the other PWN in the SMC, IKT 16 (Maitra et al 2015), bringing it within the reach of the CTA. ).…”
Section: Conclusion and Future Studiesmentioning
confidence: 75%
“…There are only two known young SMC pulsars: an 8.02 s anomalous X-ray pulsar, CXOU J010043.1-721134, with a characteristic age of ∼6700 yr (Tiengo et al 2008); The second one powers the only confirmed pulsar wind nebula (PWN) in the SMC, inside the large (74.5 pc diameter) SNR IKT 16. IKT 16 hosts a suspected pulsar with a spin-down luminosity ( E) ∼10 37 erg s −1 and an age of ∼14.7 kyr (Owen et al 2011;Maitra et al 2015). The PWN within IKT 16 was discovered with a dedicated Chandra observation, which resolved the hard (2-4.5 keV) X-ray point source seen with XMM-Newton into a faint and soft symmetric nebula surrounding a bright and hard point source.…”
Section: Introductionmentioning
confidence: 99%
“…MCSNR J0058−7217 / IKT 16 : This SNR is atypical in the SMC because of the hard extended source near its centre, suggested as the first PWN of the SMC (Owen et al 2011) and then confirmed with high-resolution Chandra observations (Maitra et al 2015). To characterise the extended soft X-ray emission from the underlying SNR, we included the pulsar and PWN components obtained in the Chandra analysis with fixed parameters in our analysis of the integrated emission.…”
Section: Notes On Individual Smc Snrsmentioning
confidence: 96%
“…In a similar manner as in B17 where the LMC radio continuum sample were investigated, we used all available radio continuum data described in various surveys to date (Filipovic et al 1997(Filipovic et al , 1998Filipović et al 2002;Payne et al 2004b;Filipović et al 2005;Reid et al 2006;Payne et al 2007;Wong et al 2011a;Crawford et al 2011;Wong et al 2011bWong et al , 2012a. Some earlier radio continuum studies of selected SMC SNRs were shown in Filipović et al (2008); Owen et al (2011);Haberl et al (2012c); Crawford et al (2014); Maitra et al (2015). Where possible, our study improves upon these previous SMC SNR studies.…”
Section: Radio Continuum Datamentioning
confidence: 96%
“…The progenitor masses implied by the SFHs associated with these remnants is consistent with theoretical work by e.g., Sukhbold et al (2016) who suggested that neutron stars are produced in SNe of stars < 30M . These four remnants have been suggested to harbour either a PWN/CCO or is associated with a Be/X-ray pulsar system (Yokogawa et al 2000;Williams et al 2006;Owen et al 2011;Haberl et al 2012b;Maitra et al 2015;Vogt et al 2018).…”
Section: Supernova Remnantsmentioning
confidence: 99%